Reef fish spawning aggregations: biology, research and management - Colin, Patrick L.; Sadovy de Mitcheson, Yvonne (Fish & Fisheries Series, 2012)
Reef fish spawning aggregations, ranging from small groups to many tens of thousands of individuals, are spectacular but poorly known natural phenomena whereby fish assemble at specific times and locations to spawn. For some species these large groups may be the only form of reproduction, the high fish numbers briefly giving a false impression of stability and abundance-an 'illusion of plenty'.  They are often a focus for intensive seasonal fishing because of their predictability and because many important commercial fishes form them. Highly vulnerable to overexploitation, many aggregations and their associated fisheries, have disappeared or are in decline. Few are effectively managed or incorporated into protected areas. Aggregations are not well understood by fishery scientists, managers and conservationists and their significance little appreciated by fishers or the wider public. To ensure their persistence to replenish important fisheries in coral ecosystems, maintain their ecosystem function and continue to delight divers, a significant change in perspective is needed to foster protection and management.   This book provides comprehensive and practical coverage of the biology, study and management of reef fish aggregations, exploring their how, when, where, and why. It explores ways to better protect, study, manage and conserve them, while identifying key data gaps and questions. The text is extensively illustrated with many unique, never before published, photographs and graphics. Case studies on over 20 interesting and important fishes are included, outlining their biology and fisheries and highlighting major concerns and challenges.